Hospitalization and thrombolysis or dual antiplatelet therapy in hemiplegic migraine patients: a cohort of 21 patients from a tertiary headache center - Roque, Alberto Jorge Castelo Branco (2024)
Introduction: Hemiplegic migraine (HM) is a rare form of migraine that closely mimics stroke, often leading to hospitalizations. In resource-limited settings, distinguishing between HM and stroke is crucial to avoid unnecessary and costly treatments such as thrombolysis (TICI) and dual antiplatelet therapy (DAPT) and their risks. Typically, with clinical and laboratory evaluations alongside computed tomography (CT), the incidence of stroke mimic admissions can be reduced to 4-6.5%. This study aimed to evaluate the hospitalization rates and use of TICI and DAPT in HM patients followed up in a tertiary headache service.   Methods: A retrospective cohort study was conducted on 21 patients diagnosed with HM at our Headache Outpatient Clinic in Fortaleza, Brazil. Data collected included demographics, clinical history, hospitalization status, and treatment details. Statistical analyses were performed to identify correlations between hospitalization and stroke treatments.   Results: The study included 21 HM patients (mean age 37.67 years, SD 9.65; 95.2% female). Hospitalization was required for 66.7% (14/21) of the patients due to suspected acute cerebrovascular events. Among hospitalized patients, 9.5% (2/21) received thrombolysis, and 14.3% (3/21) were administered DAPT, exceeding the typical stroke mimic admission rates of 4-6.5% after CT evaluation. The decision for hospitalization was strongly correlated with suspected stroke (r = 0.90) but the option to perform thrombolysis or prescribe DAPT did not correlate with any of the other variables studied.   Conclusions: Hospitalization due to suspected stroke is common among HM patients. The administration of thrombolysis and DAPT, though limited, exceeds typical rates seen in stroke care. This underscores the need for precise diagnostic criteria and cautious use of costly, risky unnecessary treatments to manage HM effectively especially in resource-limited settings.